Chłodnia, czyli grzejnia / Małgorzata Szejnert w rozmowie z Dorotą Karaś i Markiem Sterlingowem. - Szejnert, Małgorzata (1936- ) (Wydawnictwo Znak, 2026)
A book-length interview with Małgorzata Szejnert, one of Poland's most prominent reporters and writers, conducted by Dorota Karaś and Marek Sterlingow. The book explores Szejnert's life, work, and reflections on journalism, literary reportage, and the social and cultural changes in Poland from the second half of the 20th century to the present. The conversation also touches on personal themes, places important to the author such as Warsaw, Kazimierz Dolny, and Mięćmierz, and her perspective on the role of intellectuals and the media in society.